(untitled) (European Journal of Marketing and Economics, 2021)
This study tried to examine econometric analysis of local community’s perception towards protected area management in the case of Borena Sayint National park. Specifically, the study aims to estimate the direct economic value of natural forest, response on the indirect and option values and, econometric analysis of local community’s perception and/or attitude measured based on use value index. The research was conducted in Borena and Mehal Saynt Woredas with severe deforestation and biodiversity loss. Cross sectional research design and stratified-random sampling method were used, following agroclimatic zonation technique. Primary and secondary data were collected from various sources. Data were gathered from a gross total of 396 respondents. Household survey with 360 interviewees using questionnaire, key informants interview with 21 using checklist and, focus group discussion with 15 target individuals using guiding questions. Secondary data obtained from published and unpublished materials, i.e. books, journals and reports, were used. Analysis was performed using analytical tools, descriptive and order logistic regression econometric model in particular. Descriptive analyses tell us to understand the rank of community priorities of the direct, indirect and option benefits. From the direct benefits, honey, livestock, job opportunity, wood, farm tools, housing poles, tourism, timber, hunted meat, medicine, biodiversity, fruit, coffee orderly have been listed from the highest to lowest local community benefits. Similarly, common pole, biodiversity, water source, community heritage, medicine, robbery, wood fuel, carbon sequestration, tourism, livestock feed are orderly selected as their highest to lowest benefits among direct and option benefits. Hence, Local community prefers indirect benefit of park than direct benefits. The econometric analysis of local community‘s perceptions towards protected area management of the natural forest, ‘Denkoro-Chaqa’ in English means “Deaf-Forest”. Information obtained from order logistic regression (Ologit) based on response rate of households to infer the intrinsic value showed consistency between perception, selective socioeconomic and location variables. This implies that education, married, old-aged and location-2 as most important factors that respondents agreed with significant degree, and hence the most constructive idea to enhance local community`s perception in view of major conservation plans. Reputedly, family base awareness creation with formal and informal education, and other media should be done in core area, buffer zone, transitional zone areas of conservation of natural forest along with take full advantage of local community benefits.